The Role of Bacillus Subtilis Bacteria on The Growth and Production of Two Varieties of Shallots (Allium Ascalonicum L.) Asal True Shallot Seed - Rhiki Budianto; Mariani Sembiring; Yaya Hasanah (Publikasi Indonesia, 2024)
Increasing the production of shallots from True shallot seed (TSS) can be done using Bacillus subtilis bacteria. This study aims to determine the role of Bacillus subtilis bacteria on the growth and production of two shallot varieties (Allium ascalonicum L.) from True Sallot Seed. This research was conducted on Jl. Bandar Meriah, Sukamaju village, Sunggal sub-district, Deli Serdang district, with a height of 30 MDPL. This research was conducted from December 2022 to March 2023. This study used a randomised block design with two factors and three replications. The first factor is a variety of types: Sanren F-1 and Lokananta. The second factor was Bacillus subtilis bacteria with four levels: 0 ml/tanaman, 5 ml/plant, 10 ml/plant, and 15 ml/plant. The results showed that the Lokananta variety had plant heights of 5 and 7 MSPT, number of leaves 4-7 MSPT, chlorophyll B, total chlorophyll, fresh tuber weight per sample, fresh tuber weight per plot, dry tuber weight per sample and dry tuber weight per plot, Which is higher than the Sanren F-1 variety. Giving 15 ml of Bacillus subtilis bacteria/plant has tuber circumference, number of tubers per plot, weight of fresh tubers per plot, weight of dry tubers per sample, weight of dry tubers per plot, which is higher than giving bacteria of 0 ml/plant, 5 ml/plant and 10 ml/plant.